Human retinoic acid–regulated CD161+ regulatory T cells support wound repair in intestinal mucosa. (December 2018) - Povoleri, Giovanni; Nova-Lamperti, Estefania; Scottà, Cristiano; Fanelli, Giorgia; Chen, Yun-Ching; Becker, Pablo; Boardman, Dominic; Costantini, Benedetta; Romano, Marco; Pavlidis, Polychronis; McGregor, Reuben; Pantazi, Eirini; et al.
Abstract Repair of tissue damaged during inflammatory processes is key to the return of local homeostasis and restoration of epithelial integrity. Here we describe CD161+ regulatory T (Treg ) cells as a distinct, highly suppressive population of Treg cells that mediate wound healing. These Treg cells were enriched in intestinal lamina propria, particularly in Crohn's disease. CD161+ Treg cells had an all-trans retinoic acid (ATRA)-regulated gene signature, and CD161 expression on Treg cells was induced by ATRA, which directly regulated theCD161 gene. CD161 was co-stimulatory, and ligation with the T cell antigen receptor induced cytokines that accelerated the wound healing of intestinal epithelial cells. We identified a transcription-factor network, including BACH2, RORγt, FOSL2, AP-1 and RUNX1, that controlled expression of the wound-healing program, and found a CD161+ Treg cell signature in Crohn's disease mucosa associated with reduced inflammation. These findings identify CD161+ Treg cells as a population involved in controlling the balance between inflammation and epithelial barrier healing in the gut. Treg cells are essential for enforcing peripheral tolerance but can also influence tissue regeneration. Afzali and colleagues use high-dimensional analysis to describe a distinct population of CD161+ human Treg cells involved in wound healing of the intestinal mucosa.